Old Testament Theology Volume I - Preuss, Horst Dietrich (Louisville Westminster John Knox Press, 1995)
A major new work providing a comprehensive study of the theology of the Old Testament.
The author completes in this volume his comprehensive analysis of the theology of the Old Testament. Preuss focuses on a detailed assessment of Israel's responses to God's acts of election and covenant with them as a people. This volume includes a full
Keywords: Bible. -- Old Testament -- Theology. Bible. -- Old Testament. Theology